2015
DOI: 10.1111/irv.12328
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of influenza vaccination of schoolchildren in the city of São Paulo, Brazil, 2009

Abstract: BackgroundChildren play an important role in maintaining the transmission of influenza. Evidence suggests that vaccination of school-age children can reduce transmission to unvaccinated household contacts. We evaluated the direct and indirect effectiveness of the 2009 inactivated seasonal influenza vaccine in vaccinated schoolchildren and their unvaccinated household contacts.MethodsThis was a double-blind cluster randomized trial involving 10 schools and 1742 schoolchildren as well as 5406 household contacts.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…The results found in this study are compatible with the upper range of vaccine effectiveness (VE) of 42–65.0%, which was demonstrated in Hong Kong and Sao Paulo, respectively [ 10 , 11 ]. In the CDC report for seasonal influenza vaccine effectiveness in 2016–2017, adjusted vaccine effectiveness for all ages was 40%, and for age group 9–17 years vaccine effectiveness was 36% [ 12 ].…”
Section: Discussionsupporting
confidence: 88%
“…The results found in this study are compatible with the upper range of vaccine effectiveness (VE) of 42–65.0%, which was demonstrated in Hong Kong and Sao Paulo, respectively [ 10 , 11 ]. In the CDC report for seasonal influenza vaccine effectiveness in 2016–2017, adjusted vaccine effectiveness for all ages was 40%, and for age group 9–17 years vaccine effectiveness was 36% [ 12 ].…”
Section: Discussionsupporting
confidence: 88%
“…While the existing evidence demonstrates that the introduction of seasonal SIVPs can have substantial health [4][5][6][7][8][9][10][26][27][28] and economic [29,30] benefits for the wider community, this and of 27 previous studies [15,[31][32][33][34][35][36][37] suggest that the successful implementation of such programmes may depend on more qualitative, context-specific aspects. A review of SIVPs in high-income countries identified considerable administrative and logistical challenges to the successful delivery of vaccines in schools, including the choice of organisational and funding models, the logistics of vaccine supply and distribution, issues around staff capacity and workload, and communication with parents and students [35].…”
Section: Discussionmentioning
confidence: 84%
“…There is substantial evidence of indirect protective benefits to unvaccinated groups from vaccinating school-aged children [4][5][6][7][8][9][10][26][27][28][43][44][45][46][47][48][49][50]. However, the majority of evidence on the impact and cost-effectiveness of seasonal SIVPs comes from studies in North America and Europe, which have different vaccine financing mechanisms and influenza epidemiology compared to Singapore.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of cellulitis in the 6 randomized, controlled trials collated 45-50 in this review ranged from 1/143 to 1/22,070 injections with the mean being 1/5290 injections. If the 2 extreme outliers are excluded then mean prevalence of cellulitis is 1/2383 injections.…”
Section: Discussionmentioning
confidence: 99%